The co-crystal structure of etoricoxib–phthalic acid (1/1), C18H15ClN2O2S·C8H6O4 - Ma Yu-Heng; Zhu Miao-Miao; Zhang Chun-Ni; Tang Xiao-Sa; Zhang Wei-Guo; Ma Wen-Jing (Zeitschrift für Kristallographie - New Crystal Structures)
C18H15ClN2O2S·C8H6O4, triclinic, P 1‾ $\overline{1}$ (no. 2), a = 8.4340(17) Å, b = 12.172(2) Å, c = 12.816(3) Å, α = 89.98(3)° $89.98(3){}^{°}$ , β = 77.41(3)° $77.41(3){}^{°}$ , γ = 72.52(3)° $72.52(3){}^{°}$ , V = 1221.7(5) Å3, Z = 2, R gt(F) = 0.0482, wR ref(F 2) = 0.1344, T = 293 K.